1994
DOI: 10.1037/0894-4105.8.4.485
|View full text |Cite
|
Sign up to set email alerts
|

Developments in the concept of working memory.

Abstract: The authors summarize developments in the concept of working memory as a multicomponent system, beginning by contrasting this approach with alternative uses of the term working memory. According to a 3-component model, working memory comprises a phonological loop for manipulating and storing speech-based information and a visuospatial sketchpad that performs a similar function for visual and spatial information. Both are supervised by a central executive, which functions as an attentional control system. A sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
345
1
44

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 585 publications
(405 citation statements)
references
References 89 publications
15
345
1
44
Order By: Relevance
“…delayed matching to sample) that invoke working memory (Olton et al 1979). In the Baddeley and Hitch (1994) model of human short-term memory, for example, there are separate mechanisms postulated for the short-term processing of verbal and visio-spatial information, as well as a central executive to handle scheduling and controlling functions within short-term memory. As used herein, the term refers to the common denominator between the two literatures, that is, the temporary storage and use of information for immediate problem-solving.…”
mentioning
confidence: 99%
“…delayed matching to sample) that invoke working memory (Olton et al 1979). In the Baddeley and Hitch (1994) model of human short-term memory, for example, there are separate mechanisms postulated for the short-term processing of verbal and visio-spatial information, as well as a central executive to handle scheduling and controlling functions within short-term memory. As used herein, the term refers to the common denominator between the two literatures, that is, the temporary storage and use of information for immediate problem-solving.…”
mentioning
confidence: 99%
“…In this case, the subject might stop, look around for a nearby place to rest the coffee, put down the cup of coffee, open the door, and subsequently pick up the cup of coffee. In the Baddeley and Hitch view (Baddeley, 1986(Baddeley, , 1992Baddeley & Hitch, 1994), the central executive ofWM corresponds to the SAS. According to this framework, the central executive would be involved in a number of different activities: realization ofnew actions, planning and decision making, time sharing, inhibition of automatic behavior, as well as the updating and manipulation of information in WM.…”
mentioning
confidence: 99%
“…Working memory was also found to be important in this study; however, the current study adds to the literature in suggesting the degree of language demands in WM tasks is an important distinguishing quality of EF tasks in preschool children. Theoretically, the verbal WM tasks involve the 'phonological loop' as described by Baddeley and Hitch (1994). Baddeley et al (1998) have demonstrated that across early and middle childhood, vocabulary knowledge is strongly associated with "phonological loop" capacity.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible nonverbal WM may have a more general influence across all measures of EF in early childhood that could be better explored as a higher-order latent variable model. Growth in children's 'visuospatial sketchpad' capacity, as described by Baddeley and Hitch (1994), has been found to be largely dependent on maturation of visual processing centers in the right hemisphere (Barkley 1997a, b). Likewise, the use of visuo-spatial stimuli, which are less amenable to verbal encoding than conceptual stimuli (Pickering et al 2001), may help to explain these results.…”
Section: Discussionmentioning
confidence: 99%